2002
DOI: 10.1161/01.atv.0000015598.86369.04
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Actions of Peroxisome Proliferator–Activated Receptors in Lipid Metabolism and Atherosclerosis

Abstract: Abstract-Peroxisome proliferator-activated receptors (PPARs) are nuclear receptors activated by fatty acids and derivatives. Although PPAR␣ mediates the hypolipidemic action of fibrates, PPAR␥ is the receptor for the antidiabetic glitazones. PPAR␣ is highly expressed in tissues such as liver, muscle, kidney, and heart, where it stimulates the ␤-oxidative degradation of fatty acids. PPAR␥ is predominantly expressed in adipose tissues, where it promotes adipocyte differentiation and lipid storage. PPAR␤/␦ is exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
244
0
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(256 citation statements)
references
References 148 publications
(127 reference statements)
5
244
0
7
Order By: Relevance
“…Furthermore, some studies have suggested that PPARα has a direct antiatherogenic action, regulating the expression of key proteins involved in all stages of atherogenesis, including vascular inflammation [19].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, some studies have suggested that PPARα has a direct antiatherogenic action, regulating the expression of key proteins involved in all stages of atherogenesis, including vascular inflammation [19].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, nuclear receptors are associated with the regulation of metabolic homeostasis, through both the action of endosensing receptors such as LXR, FXR and PPAR (Barbier et al, 2002;Mohan and Heyman, 2003), and xenosensing receptors such as PXR and CAR (Bachmann et al, 2004;Pascussi et al, 2008;Wada et al, 2009). Thus, exposure to noncoplanar PCBs may lead to chronic activation of PXR/CAR and potential dysfunction of these metabolic processes.…”
mentioning
confidence: 99%
“…11 MetS is also known to be associated with disorders of peroxisome proliferatoractivated receptor-g (PPARg), 12 an intracellular hormone receptor with a significant role in carbohydrate and lipid metabolism. 13 PPARg agonists improve insulin resistance in patients with type 2 diabetes mellitus (DM). 14,15 Telmisartan bears a structural resemblance to PPARg agonist pioglitazone, which suggests that telmisartan may activate PPARg.…”
Section: Introductionmentioning
confidence: 99%